Формообразование прецизионных плоских оптических поверхностей при полировании - Филатов, Ю.Д. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Regularities of forming surface of the article and wear of working layer of the tool depending on process and kinematical parameters of polishing, coefficients of wear of tool material for existent technological schemes of machining have been reveale. Methods of calculations of production capacity of polishing flat precise of optical articles and filling coefficients of surface of the tool by working layer, which insure its regular wear.